Inklyuziv tálimniń innovacialıq paradigması: sociallastırıw, integraciyalıq qatnasıqlar hám imkaniyatlardı institucionlastırıw - Bekimbetova, G.R (SCIENCE and SOCIETY, 2025)
The article provides information on technologies for improving the effectiveness of inclusive and home-based education. In particular, interactive platforms and teaching methods were mentioned for engaging students with disabilities in education.
Keywords: inclusive education; children with disabilities; social and methodological actions; cooperation and motivation; platforms